Copepod-Associated Gammaproteobacteria Respire Nitrate in the Open Ocean Surface Layers - Moisander, Pia H.; Shoemaker, Katyanne M.; Daley, Meaghan C.; McCliment, Elizabeth; Larkum, Jennifer; Altabet, Mark A. (Frontiers in Microbiology, 2018)
Microbial dissimilatory nitrate reduction to nitrite, or nitrate respiration, was detected in association with copepods in the oxygenated water column of the North Atlantic subtropical waters. These unexpected rates correspond to up to 0.09 nmol N copepod-1 d-1 and demonstrate a previously unaccounted nitrogen transformation in the oceanic pelagic surface layers. Genes and transcripts for both the periplasmic and membrane associated dissimilatory nitrate reduction pathways (Nap and Nar, respectively) were detected. The napA genes and transcripts were closely related with sequences from several clades of Vibrio sp., while the closest relatives of the narG sequences were Pseudoalteromonas spp. and Alteromonas spp., many of them representing clades only distantly related to previously described cultivated bacteria. The discovered activity demonstrates a novel Gammaproteobacterial respiratory role in copepod association, presumably providing energy for these facultatively anaerobic bacteria, while supporting a reductive path of nitrogen in the oxygenated water column of the open ocean.